Plectological and molecular identification of economically important wild Russulales mushrooms from Pakistan and their antifungal potential against food pathogenic fungus Aspergillus niger (Bangladesh Journal of Plant Taxonomy, 2020)
Present study deals with the plectological and molecular analysis as well as use of economically important wild Russuloid mushrooms against food pathogenic fungus Aspergillus niger. Three different species of mushrooms viz., Russla laeta, R. nobilis, and R. nigricans were collected and identified from Himalayan range of Pakistan and are found as new records for this country. Major objective of this study was to highlight the importance of these wild creatures as antifungal agents against A. niger. For this purpose methanolic extract of selected mushrooms of different concentration levels viz., 1, 1.5, 2 and 3% were used. This activity is also first time reported from Pakistan by using this group of mushrooms. Results showed that all tested mushrooms exhibit growth inhibition of A. niger and can be used as biocontrol agents. R. nigricans showed maximum inhibition of fungus growth that is 62% at 3% concentrations while minimum inhibition was observed in R. nobilis at same concentration that is 43.6%.Bangladesh J. Plant Taxon. 27(1): 67-77, 2020 (June)